Joint optimization of dispersion matrix and 3D constellation for STSK system based on improved genetic algorithm - Xiaoping JIN; Jiayu LIU; Chen JIANG; Qiang GUO (Dianxin kexue)
Space-time shift keying (STSK) is a modulation scheme used in multi-input multi-output (MIMO) communication systems.It uses a pre-designed dispersion matrix set (DMS) to realize the flexible design of the system between multiplexing and diversity.An improved genetic algorithm (GA) was proposed to assist the joint optimization of DMS and 3D constellations, that is, the DMS and 3D constellations were jointly coded as the chromosome of GA , and the coding gain corresponding to the rank and determinant criterion was adopted as the overall fitness value.Through efficient selection and improved mutation and crossover strategies, DMS and 3D constellations with low bit error rate (BER) can be obtained.At the same time, the symmetry of the 3D constellation was used to greatly reduce the computational complexity of according to the fitness value the coding gain.The theoretical average paired error probability (ABEP) of the 3D STSK scheme was deducted.The simulation results show that, compared with the traditional GA and random search schemes, the improved GA proposed can significantly reduce the complexity of system implementation while ensuring BER performance.